Ekspresywizmy leksykalne w "Przewodniku Katolickim" z lat 1895–2005. Peiorativa pierwotne - Wiatrowski, Przemysław (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The article discusses emotive expressions that express negative emotions of the sender excerpted from "Przewodnik Katolicki" from the years 1895-2005. The author studies nominal primal negative emotional expressions that belong to the class of personal names (nomina personae), i.e. words that are semantically non-derivable and whose meanings include a fixed emotional component that is obligatory revealed in the statement. This group of units also includes words that are derived morphologically but the latter group includes only those words in which the formant is not the carrier of emotional marking. The excerpted lexical elements have been semantically analyzed. The analysis made it possible to identify their expressive meanings. In the reconstruction of their basic components (linguistic signs of emotion that are indicators and not carriers of meaning but whose signifieds correspond to a verbal proposition.), different factors that co-create the emotional value of peiorativa are considered, particularly the contextual influence. The analysis of the research material makes it possible to prove that the emotionally charged words used by the journalists writing for the weekly make their statement more powerful, add to its sharpness or pungency and, therefore, enhance the process of shaping the personal outlook of its readers.
Emotive lexical expressions in "Przewodnik Katolicki" from the years 1895-2005. Primal disparaging and derogatory words or expressions (peiorativa)
Keywords: Przewodnik Katolicki; Ekspresja językowa; Peiorativa pierwotne; Negatywne emocje